Process Integration of Supercritical CO2 Cycle and Pumped Thermal Energy Storage (PTES) System - Junrong Tang; Qibin Li; Lina Wang; Haoshui Yu (Chemical Engineering Transactions)
This work introduces a novel energy system that combines the supercritical CO2 (sCO2) cycle with Pumped Thermal Energy Storage (PTES). This integration enhances efficiency, clean energy consumption, and storage capacity, effectively managing peak loads. While it uses extra electricity during off-peak hours for energy storage, it significantly boosts output during peak demand. The system offers flexibility with a load range of 92.49-103.59 % and a round-trip efficiency of 42.61 %. Parametric analysis indicates a trade-off between efficiency and power change rate, necessitating customization based on user needs.